Induced Pluripotent Stem Cell-Based Cancer Vaccines - Ouyang, Xiaoming; Telli, Melinda L.; Wu, Joseph C. (Frontiers in Immunology, 2019)
Over a century ago, it was reported that immunization with embryonic/fetal tissue could lead to the rejection of transplanted tumors in animals. Subsequent studies demonstrated that vaccination of embryonic materials in animals induced cellular and humoral immunity against transplantable tumors and carcinogen-induced tumors. Therefore, it has been hypothesized that the shared antigens between tumors and embryonic/fetal tissues (oncofetal antigens) are the key to anti-tumor immune responses in these studies. However, early oncofetal antigen-based cancer vaccines usually utilize xenogeneic or allogeneic embryonic stem cells or tissues, making it difficult to tease apart the anti-tumor immunity elicited by the oncofetal antigens versus graft-versus-host responses. Recently, one oncofetal antigen-based cancer vaccine using autologous induced pluripotent stem cells (iPSCs) demonstrated marked prophylactic and therapeutic potential, suggesting critical roles of oncofetal antigens in inducing anti-tumor immunity. In this review, we present an overview of recent studies in the field of oncofetal antigen-based cancer vaccines, including single peptide-based cancer vaccines, embryonic stem cell (ESC)- and iPSC-based whole-cell vaccines, and provide insights on future directions.